2019
DOI: 10.1002/ppul.24506
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of time to cough resolution in children with chronic wet cough treated with antibiotics after bronchoscopy

Abstract: Background Chronic wet cough is common in pediatric pulmonology practice and is clinically important. Guidelines recommend treatment with antibiotics as their effectiveness has been proven. However, factors associated with duration of cough in response to antibiotics in children with chronic wet cough have not been prospectively examined. Objective To determine if demographic, clinical and/or bronchoalveolar lavage (BAL) factors are associated with “time to cough resolution” in children with chronic wet cough … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
(85 reference statements)
1
1
0
Order By: Relevance
“…The microorganisms most often isolated were H. influenzae , S. pneumoniae , and M. catarrhalis . These findings are consistent with data published by De Schutter et al 21 on children with recurrent pneumonia and by Wong et al 29 concerning children with chronic wet cough. Our results are also in keeping with the microbiological data reported by Chang et al, 24,30 who listed S. pneumoniae , H. influenzae , and M. catarrhalis as the most common microorganisms isolated in children with chronic wet cough.…”
Section: Discussionsupporting
confidence: 93%
“…The microorganisms most often isolated were H. influenzae , S. pneumoniae , and M. catarrhalis . These findings are consistent with data published by De Schutter et al 21 on children with recurrent pneumonia and by Wong et al 29 concerning children with chronic wet cough. Our results are also in keeping with the microbiological data reported by Chang et al, 24,30 who listed S. pneumoniae , H. influenzae , and M. catarrhalis as the most common microorganisms isolated in children with chronic wet cough.…”
Section: Discussionsupporting
confidence: 93%
“…The cough score is a verbal category descriptive score (VCD) ranging from zero (no cough) to five (cannot perform most usual activities due to severe coughing) [ 47 ]. A prospective cohort study investigated if patients’ characteristics, clinical characteristics, or additional investigation results had a correlation with cough resolution [ 48 ]. This study revealed that a significant but mild relationship exists between cough duration and cough resolution.…”
Section: Cough In Pbbmentioning
confidence: 99%